Maximizing German to English Translation Proficiency: A Bottom-Up Approach Study - Misnah Mannahali; Abd. Halim (Universitas Hamzanwadi, 2023)
In the realm of language education, the adoption of effective teaching methodologies holds paramount importance. This study addresses the discernible gap in the literature concerning the impact of a bottom-up approach on German-to-English translation. By scrutinizing the discrepancy between theories and practices, this research aims to shed light on the transformative potential of this innovative pedagogical approach. Conducted within the German Language Education Study Program at the Faculty of Language and Literature, Makassar State University, this qualitative descriptive research encompasses students enrolled in the Einfuehrung in der Uebersetzungwissenschaft (Introduction to Translation) course during the odd semester of 2020/2021. The study's focal points include assessing students' mastery of translation theory as a foundational element for achieving overarching learning objectives, examining the strategies employed by instructors in implementing the bottom-up approach, developing tailored materials designed to inspire and engage students for optimal learning outcomes, and evaluating students' proficiency in translating German texts into English following the application of the bottom-up approach. Through comprehensive assessments utilizing testing as a primary data collection method, the results unequivocally demonstrate the affirmative impact of the bottom-up approach on the translation proficiency of students in transmuting German texts into English. This study reaffirms the pivotal role of innovative pedagogical approaches in enhancing language learning outcomes and underscores the significance of incorporating the bottom-up approach into German-to-English translation courses.